Conflict Management in Schools: A Case Study of Riyadhotul Arifin Junior High School - Aprianto, Nof; Ahyani, Nur; Nugroho, Heri Setiyo (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines conflict management practices at Riyadhotul Arifin Junior High School, focusing on the role of school principals in addressing conflicts to enhance organizational performance. The research employs a literature review methodology, synthesizing insights from relevant articles and books to analyze conflict management strategies in educational settings. The findings reveal that effective conflict management requires principals to assess situational factors, including the maturity level of involved parties and the source of conflict. Passive or active approaches must be contextually applied, with an emphasis on leadership authority, behavioral influence, and power dynamics. Conflict itself is neither inherently positive nor negative; its impact depends on management effectiveness. This study highlights the nuanced application of conflict management strategies in an Islamic junior high school context, emphasizing the interplay between leadership power, subordinate attitudes, and organizational outcomes. School principals must develop strong leadership and conflict resolution skills to foster a productive school environment. Tailored strategies considering internal and external conflict sources can improve institutional performance. The research contributes to the discourse on educational leadership by outlining context-specific conflict management approaches, offering a framework for principals to balance authority, interpersonal dynamics, and organizational goals.